Ambiguous Territory - Kathy Velikov; Cathryn Dwyre; Chris Perry; David Salomon (Footprint)
What can one do when the things and processes used to sustain oneself – physically, economically, emotionally – are executed at a scale and intensity whereby they become poisonous? Such a scenario describes certain addictions. An illustration of such an addiction on a planetary scale is exemplified by the neologism agrilogistics. This planned approach to the environment seeks to organise, divide, and manage the earth in order to increase the likelihood of human survival. From parasite-vulnerable monocrops to systemic biopolitical violence upon indigenous peoples, these conditions expose the dark and unwanted externalities to the logistical algorithm that we have only recently begun to understand as deeply intertwined with each other and within all life on the planet. What can art and design do to intervene in this positive feedback loop of economic growth and environmental catastrophe? Perhaps one thing we can do is to use visual, material, and spatial media to think the world differently by questioning the premise of anthropocentrism, establishing instead new conditions of relation between human and nonhuman and with it, new forms of kinship with other species. The exhibition Ambiguous Territory: Architecture, Landscape and the Postnatural assembles a shifting tide of practices, objects, and images by architects, landscape architects, and artists that points to ways of operating within this new paradigm.